Inhibitory potency of 4- substituted sampangine derivatives toward Cu2+ mediated aggregation of amyloid β-peptide, oxidative stress, and inflammation in Alzheimer's disease. (October 2020) - Su, Chunling; Chen, Yusi; Chen, Kelin; Li, Wei; Tang, Huang
Abstract: Cu 2+ plays a key role in the pathogenesis of Alzheimer's disease (AD). The dysregulation of Cu 2+ can cause neuronal damage and aggravate development of AD. Moreover, a series of 4-substituted sampangine derivatives have been investigated as inhibitors of acetylcholinesterase and β-amyloid (Aβ) aggregation for the treatment of AD in our previous studies. In the present study, we reported that one of these derivatives SD-1 was able to modulate Cu 2+ -mediated multiple pathological elements in AD. The high selectivity of SD-1 for Cu 2+ over other biologically relevant metal ions was demonstrated by ITC. Western blotting analysis, light-scattering study, DCF-DA assay and paralysis experiment indicated that SD-1 suppressed the formation of Cu 2+ -Aβ species, alleviated the Cu 2+ -Aβ species induced neurotoxicity and inhibited the production of ROS catalyzed by Cu 2+ -Aβ species in SH-SY5Y cells over-expressing the Swedish mutant form of human APP (APPsw SH-SY5Y) and Aβ42 transgenic C elegans (CL2020). Furthermore, SD-1 inhibited the expressions of NO, iNOS, TNF-α, IL-1β and IL-6 induced by Cu 2+ in BV2 microglial cells. Collectively, these findings provided valuable insights into the design and development of potent metal-chelating agents for AD treatment. Highlights: Compound could selectively chelate Cu 2+ in the presence of other metal ions. Compound suppressed the formation of Cu 2+ -Aβ species. Compound alleviated Cu 2+ -Aβ42 induced neurotoxicity. Compound inhibited the production of ROS catalyzed by Cu 2+ -Aβ42 species. Compound inhibited the expression of pro-inflammatory cytokines induced by Cu 2+ .